Enter to the administrative race a reality (2016)
One of the most important issues of the administrative career is the entry to it and most important what the strategy and motivation should be so that any colombian citizen can carry out the activities established by law, achieve first place in a list of eligibles, to be appointed in probationary period and to demonstrate their professional and personal capacities in the labor practice within the public administration in any entity of the State.